The effect of Ag-NPs-Menthol on the Expression of Metalloproteinase in A Model-Like Osteoarthritis - Ahmadi, Maryam; Maghsoudi, Hossein; Bakhshi Khaniki, Gholamreza; Haj Hosseini, Reza; Ahangar, Parviz (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Osteoarthritis (OA) is a chronic inflammatory disease that causes dysfunction of cartilage and joints. Activation of the immune system and the development of inflammatory responses are among the main pathogenesis of the disease. Recently, it has been shown that the expression of Matrix metalloproteinase (MMPs) in patients is increased and leads to the destruction of cartilage in the joints of patients. The introduction of Nanoparticles (NPs) has transformed many fields like medicine, nutrition, and electronics. The usage of nanotechnology in medicine particularly for drug delivery is revealed to have numerous benefits. Therefore, in this study, for the first time, we evaluated the use of Menthol and silver nanoparticles on the expression of MMPs type 1, 3, 9 and 13 in OA models. Methods: BFLS cells were first incubated with LPS to induce inflammation. Then, the expression of MMPs type 1, 2, 3, and 9 was evaluated using RT-PCR, ELISA, and migration and invasion assay. This work, therefore, was aimed to synthesize Menthol-mediated silver nanoparticles and evaluate their anti-inflammatory activity. Menthol mediated silver nanoparticles were synthesized by short-term (1 day) interaction of Menthol (1 mL) with 2mM AgNO3 solution and centrifuged to obtain silver nanoparticles. Further, the menthol mediated AgNPs were evaluated for anti-inflammatory activity by in vitro method. Results: The results showed that the expression of MMPs in LPS-treated cells and silver menthol nanoparticles was decreased compared to LPS-treated cells. In addition, it was shown that menthol silver nanoparticles had the greatest reduction in MMP9 expression and reduced their migration and invasion. Conclusion: It can be said that the use of menthol silver nanoparticles can be used as a supplement along with corticosteroid and anti-inflammatory drugs and even to replace them for the treatment of OA patients, which requires further studies in the future. *Corresponding Author: Hossein Maghsoudi; Email: h.maghsoudi@pnu.ac.ir; ORCID iD: 0000-0002-1524-6420 Please cite this article as: Ahmadi M, Maghsoudi H, Bakhshi Khaniki G, Haj Hosseini R. The effect of Ag-NPs-Menthol on the Expression of Metalloproteinase in the Model-Like Osteoarthritis. Arch Med Lab Sci. 2021;7:1-13 (e11). https://doi.org/10.22037/amls.v7.34925